Tree-Ring Analysis and Genetic Associations Help to Understand Drought Sensitivity in the Chilean Endemic Forest of Nothofagus macrocarpa - Venegas-González, Alejandro; Gibson-Capintero, Stephanie; Anholetto-Junior, Claudio; Mathiasen, Paula; Premoli, Andrea Cecilia; Fresia, Pablo (Frontiers in Forests and Global Change, 2022)
Extreme drought events have increased in frequency during the 20th century triggered by global change. Thus, understanding tree-growth resilience across different terrestrial biomes has become a key goal in forest ecology. Here, we evaluate the tree-growth resilience to severe drought in the only Mediterranean-type Ecosystems of South America, using five isolated populations of Nothofagus macrocarpa. For each tree, in each sampling site, we obtained wood cores and fresh leaves for dendrochronological and population genetic analysis, respectively. An evaluation was conducted on growth resilience components in response to the most extreme drought of the 20th century in central Chile (i.e. 1968, with ~ 80% of rainfall deficit), and the influence of genetic variability, biogeography, and tree size. We hypothesize that even though current remnant populations of N. macrocarpa are small and isolated, they have locally withstood changes in climate, and that they will be genetically diverse and have a high resilience to extreme droughts. We used nuclear microsatellite markers (SSR) to estimate tree genetic variability in N. macrocarpa and investigate its correlation with phenotypic traits. We found a higher resistance in the two southernmost populations (mesic sites) than in the three northern populations (xeric sites), however those three xeric populations showed a higher recovery. In addition, a significant clear positive linear correlation between precipitation and resistance, and a negative recovery and relative resilience of tree growth to the extreme drought event of 1968 can be seen. High diversity for SSR markers was observed, although no population structure was inferred. Southern populations had a higher number of private alleles, which may be an indication of their long-lasting persistence under mesic conditions. Therefore, differences in resilience components are mainly explained by tree size and sites influences, but not genetic diversity. We concluded that observed differences in tree-growth resilience among sites can be explained by a great deal of phenotypic plasticity, fostered by genetically diverse gene pools. We advocate for a genome-wide analysis (i.e. SNP) so as to identify genomic regions correlated with phenotypic traits in order to improve the understanding of the evolutionary processes that shaped this forest resilience over time.